The Challenges and Obstacles of PPKPT in Handling Sexual Violence on Vocational Campuses - Sitepu, Hosea Sitepu; Supriadi, Supriadi (The Future of Education Journal, 2026)
Sexual violence in higher education environments, including vocational campuses, is a serious issue that requires comprehensive and sustainable handling. The Indonesian government established the Sexual Violence Prevention and Handling Task Force (PPKPT) as an institutional effort to create a safe and dignified campus environment. However, in practice, PPKPT faces various challenges and obstacles that affect the effectiveness of its duties. This study aims to analyze the challenges and obstacles faced by PPKPT in addressing sexual violence in vocational campuses (a case study of vocational schools in Aceh) using a qualitative research method with in-depth interviews. The research informants include PPKPT members, university leaders, lecturers, and students. The results of the study show that the main challenges faced by PPKPT include limited human resources and budget, low awareness among the academic community, a strong patriarchal culture, victims' fear of reporting, as well as pressure and intimidation from the perpetrators of violence. Structural barriers, such as internal institutional bureaucracy, also serve as hindrances. This study recommends strengthening PPKPT's capacity, the commitment of campus leadership, and the development of a reporting system that is safe and victim-oriented.